ALPP: anonymous and location privacy preserving scheme for mobile IPv6 heterogeneous networks1. Issue 4 (9th October 2012) - Taha, Sanaa; Shen, Xuemin (Sherman)
ABSTRACT The integration of mobile IPv6 heterogeneous networks enhances networking performance; however, it also breaks mobile node's anonymity and location privacy. In this paper, we propose an anonymous and location privacy preserving (ALPP) scheme that consists of two complementary subschemes: anonymous home binding update and anonymous return routability. In addition, anonymous mutual authentication and key establishment schemes have been proposed to work in conjunction with ALPP to authenticate a mobile node to its foreign gateway and create a shared key between them. ALPP adds anonymity and location privacy services to mobile IPv6 signaling to achieve mobile senders and receivers' privacy. Unlike existing schemes, ALPP alleviates the trade‐off between the networking performance and the achieved privacy level. Combining onion routing and anonymizer in ALPP scheme increases the achieved location privacy level where no entity in the network except the mobile node itself can identify this node's location. Using entropy model, we show that ALPP achieves higher degree of anonymity than the mix‐based scheme. The anonymous home binding update and anonymous return routability subschemes require less computation overheads and thwart both internal and external adversaries. Simulation results demonstrate that our schemes have low control packets routing delays and are suitable for the seamless handover. Copyright © 2012 John Wiley & Sons, Ltd.